Micro- and nanotechnologies in plankton research - Javeed Shaikh, Mohammed (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford OX5 1GB, England, 2015)
A better understanding of the vast range of plankton and their interactions with the marine environment would allow prediction of their large¬scale impact on the marine ecosystem, and provide in¬depth knowledge on pollution and climate change. Numerous technologies, especially lab¬on¬a¬chip microsystems, are being used to this end. Marine biofouling is a global issue with significant economic consequences. Ecofriendly polymer nanotechnologies are being developed to combat marine biofouling. Furthermore, nanomaterials hold great potential for bioremediation and biofuel production. Excellent reviews covering focused topics in plankton research exist, with only a handful discussing both micro¬ and nanotechnologies. This work reviews both micro¬ and nanotechnologies applied to broad¬ranging plankton research topics including flow cytometry, chemotaxis/toxicity assays, biofilm formation, marine antifouling/foulingrelease surfaces and coatings, green energy, green nanomaterials, microalgae immobilization, and bioremediation. It is anticipated that developments in plankton research will see engineered exploitation of micro¬ and nanotechnologies. The current review is therefore intended to promote micro¬/nanotechnology researchers to team up with limnologists/oceanographers, and develop novel strategies for understanding and green exploitation of the complex marine ecosystem.